2018
DOI: 10.1128/aem.02038-18
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Foodborne Pathogens Listeria monocytogenes and Staphylococcus aureus in Mixed-Species Biofilms Exposed to Biocides

Abstract: In nature and man-made environments, microorganisms reside in mixedspecies biofilms, in which the growth and metabolism of an organism are different from these behaviors in single-species biofilms. Pathogenic microorganisms may be protected against adverse treatments in mixed-species biofilms, leading to health risk for humans. Here, we developed two mixed five-species biofilms that included one or the other of the foodborne pathogens Listeria monocytogenes and Staphylococcus aureus. The five species, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 66 publications
(85 reference statements)
0
31
0
2
Order By: Relevance
“…Different strains of L. monocytogenes also exhibited high MBCs for PAA in the range of up to 0.5% [28,29,30,31]. In contrast, others concluded that PAA was able to significantly reduce L. monocytogenes from multispecies biofilms at 0.15% [32] and 0.3% [30], respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different strains of L. monocytogenes also exhibited high MBCs for PAA in the range of up to 0.5% [28,29,30,31]. In contrast, others concluded that PAA was able to significantly reduce L. monocytogenes from multispecies biofilms at 0.15% [32] and 0.3% [30], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Different strains of L. monocytogenes also exhibited high MBCs for PAA in the range of up to 0.5% [28,29,30,31]. In contrast, others concluded that PAA was able to significantly reduce L. monocytogenes from multispecies biofilms at 0.15% [32] and 0.3% [30], respectively. The MIC of PAA for other organisms seemed to be much lower, in the range of 0.01–0.03% for Gram-positive and Gram-negative flora isolated from citrus fruit [33], 0.0003% for Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa [34], and 0.0001–0.001% for P. aeruginosa , S. aureus , E. coli , and S. epidermidis [35].…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm is an association of microorganisms that are firmly attached to the biotic or abiotic surface, encased within an extracellular polymeric substance (EPS) matrix, and that can show new character with respect to gene expression, protein synthesis, growth rate, and metabolic activities [44,45]. Biofilm production can be influenced by a number of factors such as surface conditions, chemical and physical growth factors, cellular structures, and any other challenges.…”
Section: Stages Of Biofilm Developmentmentioning
confidence: 99%
“…Biofilms are reportedly behind the pathogen's increased tolerance to quaternary ammonium compounds due to changes in membrane fluidity [75]. Biofilms can also protect L. monocytogenes from the action of biocides, but the underlying mechanism of biocide protection is yet to be clarified [76].…”
Section: Persister Cells and Biofilm Formationmentioning
confidence: 99%